2006
DOI: 10.1095/biolreprod.105.045930
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous Inactivation of Sox9 Causes Complete XY Sex Reversal in Mice1

Abstract: In the presence of the Y-chromosomal gene Sry, the bipotential mouse gonads develop as testes rather than as ovaries. The autosomal gene Sox9, a likely and possibly direct Sry target, can induce testis development in the absence of Sry. Sox9 is thus sufficient but not necessarily essential for testis induction. Mutational inactivation of one allele of SOX9/Sox9 causes sex reversal in humans but not in mice. Because Sox9(-/-) embryos die around Embryonic Day 11.5 (E11.5) at the onset of testicular morphogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
247
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(261 citation statements)
references
References 32 publications
11
247
1
2
Order By: Relevance
“…Many studies on testis-determining factors such as Dmrt1 and Sox9 have previously been conducted in mammals and birds (Barrionuevo et al, 2006;Smith et al, 2009). Dmrt1 445 appears to be involved in a certain type of XY sex reversal in humans (Bennett et al, 1993;Flejter et al, 1998;Raymond et al, 1999b;Veitia et al, 2001).…”
Section: Gsdf Induces Testis-differentiating In the Tilapiamentioning
confidence: 99%
“…Many studies on testis-determining factors such as Dmrt1 and Sox9 have previously been conducted in mammals and birds (Barrionuevo et al, 2006;Smith et al, 2009). Dmrt1 445 appears to be involved in a certain type of XY sex reversal in humans (Bennett et al, 1993;Flejter et al, 1998;Raymond et al, 1999b;Veitia et al, 2001).…”
Section: Gsdf Induces Testis-differentiating In the Tilapiamentioning
confidence: 99%
“…SOX9 can antagonize β-catenin function in chondrocytes (Akiyama et al, 2004) and intestinal epithelium (Bastide et al, 2007), however its action on Wnt/β-catenin pathway in the developing gonad has not been thoroughly investigated so far. It is interesting to note that, in XY Sox9 -/-mice, in the presence of Sry, two ovarian genes, Wnt4 and Foxl2 are expressed (Barrionuevo et al, 2006), indicating that Sox9 alone maybe responsible for the downregulation of Wnt4 or Foxl2 in the XY gonad.…”
Section: Is Wnt/β-catenin the Proposed "Z" Factor?mentioning
confidence: 99%
“…Indeed, studies have shown significant functional redundancy between these factors (Bylund et al, 2003;Cheung and Briscoe, 2003;Graham et al, 2003;Taylor and LaBonne, 2005;Kellerer et al, 2006). Within the male genital ridge, Sox8 and Sox9 gene expression are up-regulated as a consequence of Sry expression (Sekido et al, 2004) and influence male sex determination and pre-Sertoli cell differentiation (Sock et al, 2001;Takada and Koopman, 2003;Chaboisser et al, 2004;Barrionuevo et al, 2006). Several studies have shown that Sox8 and Molecular Reproduction and Development.…”
Section: Genital Ridge Expression Of Selectedmentioning
confidence: 99%